YOUTH ECONOMIC INDEPENDENCE AND IDENTICAL SELF-IDENTIFICATION PROCESS: SOCIAL AND PSYCHOLOGICAL FACTORS - Xoshimov, Hakimjon (UZBEKISTAN — 2030: PROSPECTS FOR INNOVATION, SCIENCE AND EDUCATION, 2025)
This thesis explores the processes of economic independence and self-identification among youth. It focuses on the impact of economic independence on young people's self-awareness, as well as social and psychological factors such as relationships with parents, societal stereotypes, and the education system. The thesis analyzes the role of economic independence in the process of self-identification among youth and its influence on their social and psychological development.